Design and Build an Asset Management System at PT. Fajar Solusi Elektronik - Febrian Saputra; Sharyanto Sharyanto; Bernadus Gunawan Sudarsono (Jurnal Sains dan Teknologi Widyaloka (JSTekWid), 2023)
PT. Fajar Solusi Elektronik  is one of the medium to lower scale cooperatives based in the city of Jakarta. The large number of goods in the company will certainly be difficult to manage, care for, and maintain the assets of the goods owned by the company. Goods assets that exist in PT. Fajar Solusi Elektronik includes computers, laptops, tablets, printers, speakers and other supporting tools. Currently, the management of the asset lending process still uses paper manuals and individual memories, while there are many assets, there is no notification feature if there is a return of goods, so that errors in calculating goods often occur, the data obtained has not been managed properly, so data loss often occurs. Still manually using paper and goods data, data on the distribution of goods assets to reports have not been stored and organized properly. For analysis and design methods use the Unfield Modeling Language (UML). This asset management information system uses the PHP programming language and MySQL as its database. With this web-based asset management information system, the processes related to asset management are easier to use, accurate and integrated.